2018
DOI: 10.1186/s12880-018-0259-3
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasonography of the pancreas shows impaired perfusion in pancreas insufficient cystic fibrosis patients

Abstract: BackgroundPerfusion assessment of the pancreas is challenging and poorly evaluated. Pancreatic affection is a prevalent feature of cystic fibrosis (CF). Little is known about pancreatic perfusion in CF. We aimed to assess pancreatic perfusion by contrast-enhanced ultrasound (CEUS) analysed in the bolus-and-burst model and software.MethodsWe performed contrast enhanced ultrasound of the pancreas in 25 CF patients and 20 healthy controls. Perfusion data was analysed using a dedicated perfusion model providing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Thus, Yung et al (58) concluded that insulinopenia plays a prominent role in the pathogenesis of glucose intolerance and subsequent development of CF-associated diabetes. Engjom et al (17) measured perfusion of the pancreas in pancreas deficient patients with CF using contrast-enhanced ultrasonography. Pancreas insufficient patients with CF had longer mean transit times (P Յ 0.002), lower blood flow (P Ͻ 0.001), and lower blood volume (P Ͻ 0.05) compared with healthy controls and pancreas-sufficient patients with CF.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Yung et al (58) concluded that insulinopenia plays a prominent role in the pathogenesis of glucose intolerance and subsequent development of CF-associated diabetes. Engjom et al (17) measured perfusion of the pancreas in pancreas deficient patients with CF using contrast-enhanced ultrasonography. Pancreas insufficient patients with CF had longer mean transit times (P Յ 0.002), lower blood flow (P Ͻ 0.001), and lower blood volume (P Ͻ 0.05) compared with healthy controls and pancreas-sufficient patients with CF.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements using absolute perfusion estimation should be independent of patient-and equipmentrelated factors. Though not demonstrated in the bowel, studies suggest that the interobserver data for this method is promising (Engjom et al 2018) and that you can indeed compare perfusion parameters between different scanners (Stangeland et al 2017). Currently there are no commercial systems providing these data and since the post-processing is cumbersome, it is primarily a research tool.…”
Section: Blood Flowmentioning
confidence: 99%
“…Others demonstrated that the CF pancreas in insufficient subjects was softer compared to sufficient subjects by using Acoustic-Radiation-Force-Impulse (ARFI)-Imaging, maybe suggesting that fat rather than fibrosis is the dominating feature [ 18 ]. We recently demonstrated reduced perfusion of the CF pancreas, indicating reduced vascularity of the affected pancreas [ 19 ]. In this study we did not perform complementary US modalities.…”
Section: Introductionmentioning
confidence: 99%